2009
DOI: 10.1007/s11249-009-9480-0
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Characterization of Several Silicon-Based Materials Under Ionic-Liquids Lubrication

Abstract: The tribological behaviors of three siliconbased materials (low temperature silicon oxide (LTO), polysilicon (Poly Si) and silicon nitride (Si 3 N 4 ) films) under ion liquids (ILs) lubrication have been investigated by varying the applied load and the sliding velocity. An atomic force microscope and a nanoindentor were used to characterize the deposited films, and the worn surfaces after frictional tests were analyzed by an optical microscope, a scanning electron microscope (SEM) with an energy dispersive spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…4 Boron 1s XPS spectra showing a neat 1-methyl-3-hexylimidazolium tetrafluoroborate on Au, b sliding of sialon against steel lubricated with 1-methyl-3-hexylimidazolium tetrafluoroborate leads to the formation of BN protective film, and c sliding of sialon against Si 3 N 4 lubricated with 1-methyl-3-hexylimidazolium tetrafluoroborate leads to the formation of B 2 O 3 and BN films [22] resistance compared to the conventional lubricants X-1P (a phosphazene type lubricant) and an unidentified PFPE [55]. Ball-on-disk studies have also been made on various ILs coated on various silicon surfaces, such as surfacemodified silicon (hydroxyl and amino-terminated surfaces), polysilicon, SiO 2 , and Si 3 N 4 , where it was found that longer alkyl chains in the cation and the hydrophobic anions exhibit desirable tribological properties [64,65]. Bermudez and coworkers reported pin-on-disk results on the application of ILs as lubricants for various polymers and polymer composites, such as those based on polystyrene, polycarbonate, and polyamides [46,47].…”
Section: Lubrication Using Ilsmentioning
confidence: 99%
“…4 Boron 1s XPS spectra showing a neat 1-methyl-3-hexylimidazolium tetrafluoroborate on Au, b sliding of sialon against steel lubricated with 1-methyl-3-hexylimidazolium tetrafluoroborate leads to the formation of BN protective film, and c sliding of sialon against Si 3 N 4 lubricated with 1-methyl-3-hexylimidazolium tetrafluoroborate leads to the formation of B 2 O 3 and BN films [22] resistance compared to the conventional lubricants X-1P (a phosphazene type lubricant) and an unidentified PFPE [55]. Ball-on-disk studies have also been made on various ILs coated on various silicon surfaces, such as surfacemodified silicon (hydroxyl and amino-terminated surfaces), polysilicon, SiO 2 , and Si 3 N 4 , where it was found that longer alkyl chains in the cation and the hydrophobic anions exhibit desirable tribological properties [64,65]. Bermudez and coworkers reported pin-on-disk results on the application of ILs as lubricants for various polymers and polymer composites, such as those based on polystyrene, polycarbonate, and polyamides [46,47].…”
Section: Lubrication Using Ilsmentioning
confidence: 99%
“…Xie et al [13] demonstrated that the application of external electric fields could evidently increase the film thickness of ionic liquids formed between nanogaps. Other researchers also demonstrated that friction and wear properties of some ionic liquids were better than many traditional lubricants [14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Silicon is another important material used in the manufacture of micro-and nano-electrical and mechanical systems (MEMS/NEMS), where the demand for conductive lubricants has increased. [21] Several research groups have been successfully testing the performance of pure ILs as lubricants for Si surfaces [22][23][24][25][26] but, to our knowledge, the only reports on the efficient behavior of ILs as oil additives to lubricate Si were recently published by the group of T. Atkin. [27,28] Sulfur-based organic salts were tested in our laboratory as additives in the base oil polyethylene glycol (PEG200) to lubricate Si substrates aiming at a future application in MEMS/ NEMS, which involve moving parts.…”
Section: Introductionmentioning
confidence: 99%